Theoretical Analysis of Gamified Music Application for Cultivating Intrinsic Motivation in Music Education - He, Xuan (Journal of Educational Theory and Practice, 2026)
The present study explores the traditional music teaching method known as instrumental music teaching and discusses the drawbacks related to the repetitive nature of training and the lack of prompt feedback. Beginner students who learn how to play musical instruments like piano and flute usually have trouble overcoming their struggles while studying music, resulting in higher rates of music course dropouts. In order to solve this problem, the study creates a model for music teaching methodology, using the concept of game elements that comes from an extensive literature review. The theoretical background is based on the Self-Determination and Flow theories. There are four main dimensions in the model, including: 1) student learning profiles; 2) step-by-step resource allocation; 3) individual-based teaching process; 4) multidimensional evaluation process. The goal of the study is to create an effective approach to motivating learners intrinsically. Additionally, the study offers an outlook on the future development of collaboration between humans and machines in the field of music.